Studying results of life quality changes among children of the first three years of life with visual analyzer congenital pathology - Medvedovskaya, Natalya; Barinov, Yury; Bukhanovskaya, Tatyana; Shevchik, Anatoly (ScienceRise: Medical Science, 2017)
Aim: the study of changes of life quality components in children of the first three years of life with the congenital pathology of the visual analyzer as an instrument of formation of their social adaptation in future. Materials and methods: forms of the sociological study by the adapted version of the standardized Children’s Visual Function Questionnaire (CVFQ) Felius et al. (2004) – 498 forms, among them 398 – from the main group and 100 – from the control one were the initial material. The scientific base of the study was ambulatory-polyclinic departments of health protection institutions of the city Kyiv that give medical care to children of the first three years of life, especially with the congenital pathology of the visual analyzer. To achieve the aim, it was necessary to use the complex of research methods, based on the system approach, namely: medical-statistical and sociological methods (form questionnaire with the interim report about the aim and tasks of the study for respondents, previous oral voluntary consent for the participation in the anonymous questionnaire). Results: It was elucidated, that most respondents from the main group, as opposite to patients from the control one, had disorders of life quality components by the scale “general vision” and “influence on a family”. Parents of children from the control group estimated the general vision of their children totally in 89,75 ± 1,33 points against 60,25 ± 1,96 by the total estimation of parents of children from the main group (difference was 32,87 %, at р<0,001). In general, the total number of points in the main group was 64,89 ± 1,01 in the main group against 84,67 ± 0,92, by total estimations of the life quality of children of the early age by parents with the difference in 23,4 % (р<0,001). The results of the realized study prove changes of the children’s life quality at vision disorders in the early age that substantiates the expedience of intensifying arrangements on timely revelation and treatment of vision function disorders in children, according to existent medical-technological documents. Conclusions: the studies proved that children with the congenital pathology of the vision analyzer suffer from the loss of life quality components from the early age that motivates the interaction between a family doctor, child ophthalmologist within their competences in giving medical help at vision analyzer function disorders from the first days of child’s life, for realizing the effective supervision of a family, preventing the development of the medical-social maladjustment of both a child itself and its family